Factors affecting adherence to a gluten-free diet in children with celiac disease. Issue 6 (1st June 2014) - MacCulloch, Katherine; Rashid, Mohsin
Abstract: BACKGROUND: The treatment of celiac disease is a strict, life-long gluten-free (GF) diet. This diet is complex and can be challenging. Factors affecting adherence to the GF diet are important to identify for improving adherence. OBJECTIVE: To identify factors that inhibit or improve adherence to a GF diet in children with celiac disease. METHODS: Patients (<18 years of age) with biopsy-confirmed celiac disease followed by the gastroenterology service at a tertiary care paediatric institution were surveyed using a mailed questionnaire. Factors influencing adherence to a GF diet were scored from 1 to 10 based on how often they were problematic (1 = never, 10 = always). Parents of patients <13 years of age were instructed to complete the survey with their child. Adolescents ≥13 years of age were asked to complete the survey themselves. RESULTS: Of 253 subjects, 126 completed the survey; the median age was 12 years (range two to 18 years). Forty percent were adolescents. Overall, participants reported good adherence at home and school, but lower adherence at social events. Adolescents reported lower adherence compared with parents. Availability of GF foods and cost were the most significant barriers. Other factors identified to help with a GF diet included education for schools/restaurants and improved government support. CONCLUSIONS: Availability, cost and product labelling are major barriers to adherence to a GF diet. Better awareness, improved labelling and income support are needed to help patients.